2018
DOI: 10.5194/cp-2018-92
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing and Structure of the 4.2 ka BP Event in the Indian Summer Monsoon Domain from an Annually-Resolved Speleothem Record from Northeast India

Abstract: 35Clim. Past Discuss., https://doi

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Recently, two additional speleothem records have been published from Mawmluh Cave that span the time interval of the 4.2‐ka event (Kathayat et al ., ). These new δ 18 O profiles from stalagmite samples ML.1 and ML.2 share some similarities with the KM‐A record but also show differences.…”
Section: The New Holocene Subdivisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two additional speleothem records have been published from Mawmluh Cave that span the time interval of the 4.2‐ka event (Kathayat et al ., ). These new δ 18 O profiles from stalagmite samples ML.1 and ML.2 share some similarities with the KM‐A record but also show differences.…”
Section: The New Holocene Subdivisionsmentioning
confidence: 99%
“…It has been termed the “Holocene Turnover” (Paasche et al ., ) that subsequently resulted in the establishment of a new climatic regime or mode (Paasche and Bakke, ), or the “4.07 ka BP climatic anomaly” in southern Africa (Railsback et al, ). The event appears to be global in nature, occurring in proxy records across seven continents from North America and northern Europe, through the Mediterranean, Middle East (Weiss, , 2017a) and India (Berkelhammer et al ., ; Kathayat et al ., ) to China (Cai et al ., ; Zhang et al ., ) and Australia (Denniston et al ., ); and across Africa (Chase et al ., ; Ruan et al ., ), Andean–Patagonian South America (Schimpf et al ., ), and Antarctica (Peck et al ., ). In the North Atlantic and western Canada, the event is reflected in atmospheric and oceanic cooling (Gkinis et al ., ; Orme et al ., ; Zhang et al ., ) and so‐called “neoglaciation” with glacier readvances (Balascio et al ., ; Geirsdóttir et al ., ; Menounos et al ., ), while in the mid‐ and low latitudes across both hemispheres it is marked by aridification (Booth et al ., ; Wanner et al ., ).…”
Section: The New Holocene Subdivisionsmentioning
confidence: 99%
“…The monsoon system directly and/or indirectly controls the hydrology, economy, culture, society, land use, vegetation, etc., across the Indian subcontinent. Earlier studies on palaeomonsoons indicate that several ancient civilisations suffered due to the adverse changes in the Indian monsoon causing severe drought and/or floods (Staubwasser et al, 2003;Rashid et al, 2011;Gupta et al, 2013;Lone et al, 2014;Partin et al, 2015;Kathayat et al, 2018;Band et al, 2018;Gautam et al, 2019). Hence, a clear long-term understanding of Indian monsoon variability is of vital interest for a better understanding of ocean circulation and ocean-atmosphere interactions in the past and for better predictions of the monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Several other paleo-archives recovered around Asia (Kaniewski et al, 2018;Kathayat et al, 2018), Europe (Zanchetta et al, 2016) and Africa (Gasse, 2000) show this drier event between 4.2 and 3.8 ka BP. Arz et al (2006) suggested that the 15 environmental changes around 4.2 ka BP is an expression of a major drought event, which strongly affected Middle East agricultural civilizations.…”
Section: The Event 20mentioning
confidence: 86%